Elaboration and implementation of a didactic guide with technical medical vocabulary activities through the moodle platform to enhance reading comprehension at the third level of the faculty of medicine at the university of cuenca during the school year 2015-2016. - Segarra Lazo, Sandra Noemí (2016)
The present study established the effectiveness of the elaboration and implementation of a didactic guide with vocabulary learning strategies and activities through the Moodle platform to enhance reading comprehension of medical intermediate students at the University of Cuenca. The study explored the various strategies that were employed to learn medical vocabulary through the reading comprehension and concentrates on three specific strategies: contextual guessing, inferring and word formation of medical vocabulary. In order to investigate academic English language needs of medical learners, a. mixed-method research was conducted by means of pretest, posttest and observation templates. Data were analyzed both quantitatively and qualitatively. English was considered highly important to carry out various activities in the medical field. The findings portrayed that Technical medical vocabulary activities improve the reading comprehension skill in medical topics; therefore, it is important to include medical topics in the English courses to meet students' needs in their future studies abroad. The findings provided recommendations for designing course contents that integrate with enriched knowledge of all four skills of the English language with a close emphasis on the receptive skill reading comprehension.